2016
DOI: 10.1002/wcms.1248
|View full text |Cite
|
Sign up to set email alerts
|

State‐specific multireference perturbation theory: development and present status

Abstract: The state-specific multireference perturbation theory (SSMRPT), which provides one state at a time may now gradually become a new useful ab initio tool for studying electronic states with strong configurational quasidegeneracy owing primarily to its suitability toward numerical implementation in the presence of intruders and also to a great extent for its firm theoretical construct and the scope of a systematic and hierarchical improvement. The method works with a complete active space, and treats each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 127 publications
(310 reference statements)
0
25
0
Order By: Relevance
“…In this study we also develop relaxed DSRG-MRPT2 and MRPT3 approaches in which the reference wave function is optimized under the effects of dynamic electron correlation. Most statespecific MRPT2 approaches, including CASPT2 and NEVPT2, do not account for reference relaxation effects, with the notable exception of Mukherjee's state-specific MRPT2, [65][66][67][68][69] generalized Van Vleck PT2, [70][71][72][73] and multiconfigurational PT2. 68,74,75 We begin our discussion of DSRG-MRPT3 by providing a brief overview of the general MR-DSRG ansatz in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we also develop relaxed DSRG-MRPT2 and MRPT3 approaches in which the reference wave function is optimized under the effects of dynamic electron correlation. Most statespecific MRPT2 approaches, including CASPT2 and NEVPT2, do not account for reference relaxation effects, with the notable exception of Mukherjee's state-specific MRPT2, [65][66][67][68][69] generalized Van Vleck PT2, [70][71][72][73] and multiconfigurational PT2. 68,74,75 We begin our discussion of DSRG-MRPT3 by providing a brief overview of the general MR-DSRG ansatz in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of various MRPT methods can be found in Ref. . It is known that they have different strengths and weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Designing methods which can accurately treat MR‐systems at an affordable computational price present a challenge to the practitioners of electronic structure theory . Various workers in the realm of electronic structure theory have suggested different approaches to address these problems .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well‐established MRPT2 methods, there has been recent development of new emerging approaches to add dynamic correlation effects to multiconfigurational wave functions. Among them are the Van Vleck perturbation theory , the canonical transformation theory , the GASPT2 (second‐order perturbation theory for generalized active‐space self‐consistent‐field wave functions) , the SplitGAS and new developments of state‐specific MRPT . In addition, efficient approximations have been introduced to reduce the computational cost and provide favorable scalability, for example the frozen natural orbital complete active‐space second‐order perturbation theory method (FNO‐CASPT2) and the domain‐based local pair natural orbital theory applied to the NEVPT2 method .…”
Section: Introductionmentioning
confidence: 99%